PENANAMAN NILAI “ADAT BASANDI SYARAK, SYARAK BASANDI KITABULLAH” MELALUI PEMBELAJARAN PKBAM DI SMP NEGERI 1 BUKITTINGGI - Neldawati Neldawati; Darul Ilmi (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Character education is the most important thing in shaping students' personalities. In forming this personality, every Minang person adheres strictly to the Minang philosophy. This philosophy is Adat Basandi Syarak, Syarak Basandi Kitabullah. However, recently this philosophy is only known as a term or jargon. The younger generation does not know the values, philosophy and essence of these terms. So that this philosophy becomes the personality of students as the younger generation, the Bukittinggi city government has included these values in the Minangkabau Natural Cultural Character Education (PKBAM) subject. This article discusses the implementation of PKBAM at SMPN 1 Bukittinggi. Starting from learning materials in class, character building through the P5 project, implementation of wearing traditional clothes as one of the mandatory uniforms, practice and familiarization with Minangkabau cultural values.